Finite element analysis of an automated rapid maxillary expander (ARME) - Zabir, F.A.; Abdullah, A.S.; Abu Osman, Noor Azuan; Radzi, Z.; Yahya, N.A.; Abu Kasim, Noor Hayaty (SPRINGER, 233 SPRING STREET, NEW YORK, NY 10013, UNITED STATES, 2008)
An Automated Rapid Maxillary Expander (ARME), is a specially designed orthodontic appliance to overcome the shortcomings imposed by the traditional butterfly expansion appliance. It operates by automatically widening the maxilla (upper jaw) by expanding the midpalatal suture [1]. This procedure is not feasible after late teenage years due to more rigid facial skeleton features. According to the study by Cozzani [2], the activation of the device could produce 0.25 mm of expansion per day. Over the period of 2 weeks, the expansion produced is up to 7 mm in total [1]. For this study, we explored the mechanism involved in the ARME appliance by using Finite Element Modeling method.